Constructing the Folk Cultural Sphere: Agency, Media and Authority. Issue 1 (30th June 2021) - ,
Abstract : This paper explores the dynamics of agency, media and authority in the maintenance and construction of the folk cultural sphere – that is, a society's generalized perception and understanding of traditional culture. The phenomenon is explored through a series of cases, organized chronologically, on: medieval manuscript technologies and Snorri Sturluson's Edda; seventeenth- and eighteenth-century written representations of Sámi; a nineteenth-century living ethnographic exhibition of Sámi; current fieldwork documenting Rotenese and Tetun traditions in Indonesia; a community-driven living ethnographic exhibition on the island of Java. The final discussion takes an overview of the perspectives gained from the individual cases to consider their broader implications.